The Transition of the Sou Upaa Language in Hatuolo Village - Itihuny, Calvin; Pattiasina, Petrus Jacob; Hiariej, Crissanty (Universitas Pattimura, 2023)
This research aims to describe the level of shift in the Sou Upaa language and explain the factors causing the shift in the Sou Upaa language in Negeri Hatuolo, North Seram District, Central Maluku Regency, using sociolinguistic studies. This type of research uses qualitative and quantitative research designs. The data source for this research is parents as the main data source, namely 8 interview informants. Data collection techniques in this research include observation techniques, interview techniques, questionnaire techniques, recording techniques and documentation. The research instruments used were note sheets/books, questionnaires, recording and documentation. Data analysis techniques using data transcription and data reduction, namely observation, interviews, field recording and documentation, identifying and analyzing qualitatively and quantitatively then drawing conclusions. Checking the validity of the data uses triangulation of sources, methods and theories.The research results show that, data on Sou Upaa language shift among children and young people aged 30 and under, 1) family, namely parents when communicating with children in the family and teaching children not to use Sou Upaa language or not. always use Ambon Malay, 2) Education is not taught to use Sou Upaa language, but always use Indonesian, 3) Migration or Hatuolo people who come down to coastal countries with demands for education, go abroad, work again always use Ambon Malay. Family Factors Migration Factors, Educational Factors and wild environments. Migration Factors, Economic Factors and School Institutional Factors. Sou Upaa language shifts at the age of children and young people, the family domain is 100%, the neighbor domain is 100%, the social domain is 100% and the government domain is 100%. Keywords: Sou Upaa Language Shift in Hatuolo Country, (sociolinguistic study).